Analysis of factors forming the students’ business interests at Vocational High School 2 Payakumbuh - Maulana, Fajar; Wakhinuddin, Wakhinuddin; Giatman, M.; Edidas, Edidas (Jurnal Pendidikan Teknologi Kejuruan, 2020)
This study aims to ascertain the Forming Factors of Business Interest of Students in the Department of Light Vehicle Engineering at Vocational High School 2 Payakumbuh based on the internal factors: (1) Education, (2) Personality, (3) Motivation, (4) Experience, (5) Knowledge, (6) Opportunities, (7) Commitment, (8) Discipline, and (9) Leadership. This type of study was quantitative descriptive. The study population was all TKR Department students in the academic year 2019/2020 consisting of 110 students. Then, there were 85 students as samples, using the Slovin formula with a precision of 5%. Data analysis techniques are descriptive analysis and confirmatory analysis for hypothesis testing. Confirmatory analysis there are 9 independent variables analyzed through Anti Image Matrix Analysis, from the results of the research trial there are 2 variables: Education and Knowledge have MSA scores that do not meet the requirements: 0.338 <0.500 and 0.353 <0.500 so only 7 variables for further analysis. In the analysis of communilities there are 3 variables which have values ​​below 0.500, namely Personality: 0.477, Experience: 0.306 and Commitment: 0.475, then this variable is discarded. The results of the analysis of the research trials formed a factor group of 3.128 which means that the factor was able to explain 78.2% of the 4 variables, and 21.8% of the other variables. It can be concluded that there are 4 variables: motivation, opportunity, discipline, and leadership which are the most dominant factors.